Assessing Teachers’ Perceived Readiness and Attitude toward AI Integration in Creating Learning Materials at Samal National High School–Main - Ronnel Maghanay; Noemhay Mojica; Rana Reem Teodoro; Vanessa Dungca; Mildred Esperanza; Camille Tipay; Romeo Quintos jr. (Indonesian Journal of Teaching and Learning (INTEL), 2026)
Purpose –The rapid integration of Artificial Intelligence (AI) in education is reshaping teaching and learning by enabling individualized instruction and enhancing curriculum development. This study examined the perceived readiness and attitudes of 69 teachers at Samal National High School–Main toward AI integration in developing instructional materials during the 2025–2026 academic year. Methodology – A descriptive–correlational survey design was employed using a validated instrument adapted from Fundi, Sanusi, Oyelere, and Ayere (2024) on a 5-point Likert scale. Findings – Results showed high levels of readiness (M = 3.65) and very positive attitudes (M = 4.30) toward AI, though formal AI training participation was low (M = 2.55). A strong, positive, and significant correlation was found between readiness and attitude (r = .749, p < .001). These findings suggest that teachers are prepared to adopt AI in instructional design, but structured professional development and institutional support are essential. Novelty – This study provides localized empirical evidence on the relationship between teachers’ readiness and attitudes toward AI integration specifically in instructional material development within a public secondary school context. Significance – The study provides insights for teacher training programs, policy development, and strategic implementation of AI to enhance educational outcomes.